DEVELOPMENT DIRECTIONS OF PROFESSIONAL COMPETENCIES OF FUTURE TEACHERS IN THE CONTEXT OF THE PEDAGOGICAL EDUCATION INNOVATION CLUSTER (World Bulletin of Education and Learning, 2025)
The rapid modernization of the educational system requires the transformation of teacher preparation models, emphasizing the continuous development of professional competencies aligned with the demands of innovative pedagogical environments. The pedagogical education innovation cluster serves as an integrative platform that unites higher education institutions, general education schools, research centers, and social partners to ensure practical, interdisciplinary, and technology-driven professional formation of future teachers. This article examines the developmental directions of professional competencies of future teachers within such a cluster-based approach, focusing on the pedagogical ecosystem formed through collaboration, resource sharing, and coordinated educational policies. Key components analyzed include competency-based curriculum design, practice-oriented teaching, digital pedagogy, reflective learning, research integration, and inclusive education practices. The study highlights that professional competencies are not limited to subject mastery but encompass soft skills, leadership abilities, ethical responsibility, and readiness for innovation. Findings demonstrate that innovation clusters enhance the professional training of student-teachers through authentic learning experiences, co-creation opportunities, and exposure to real classroom challenges. The cluster also strengthens cooperation between universities and schools, fosters creative pedagogical solutions, and accelerates the adoption of modern teaching technologies. The results provide a conceptual basis for improving teacher education quality, supporting pedagogical reforms, and addressing the evolving needs of contemporary learners and society.
Keywords: Professional competencies, future teachers, innovation cluster, pedagogical education, cooperation, practical training, digital pedagogy, reflective practice, teacher preparation, professional development.